2017
DOI: 10.1111/lang.12251
|View full text |Cite
|
Sign up to set email alerts
|

Early Language Learning: The Impact of Teaching and Teacher Factors

Abstract: This study examined the progress in lexical and grammatical knowledge among 252 learners of French in England across the last two years of primary education and into the first year of secondary school in relation to teaching and teacher factors. It compared linguistic outcomes from two different approaches, one which emphasized oracy and the other which combined literacy with attention to oracy development. We also explored the relationship between linguistic outcomes and other teaching/teacher factors: teachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 31 publications
0
26
0
2
Order By: Relevance
“…More fine‐grained analyses are needed to investigate the effect of teaching practices on language learning if researchers want to deepen their understanding of the effect of instruction. Although research is starting to show the impact that teachers’ language proficiency can have on language learning outcomes (see Graham et al., , for an example), little is actually known about teachers’ “abilities, level of training, methodological knowledge and language proficiency” (Jaekel et al., , p. 636).…”
Section: Limitations and Future Workmentioning
confidence: 99%
See 2 more Smart Citations
“…More fine‐grained analyses are needed to investigate the effect of teaching practices on language learning if researchers want to deepen their understanding of the effect of instruction. Although research is starting to show the impact that teachers’ language proficiency can have on language learning outcomes (see Graham et al., , for an example), little is actually known about teachers’ “abilities, level of training, methodological knowledge and language proficiency” (Jaekel et al., , p. 636).…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Evidence has been growing that it is not an early start but length and amount of instruction (i.e., hours per week) that are determinant variables in foreign language learning (Graham, Courtney, Marinis, & Tonkyn, ; Muñoz, , ; Webb & Chang, ). In two studies, Muñoz showed that it was length of instruction and exposure to foreign language input and not an early start that were determinant predictors for learners’ speaking performance (Muñoz, ), on the one hand, and for their general language proficiency and vocabulary knowledge (Muñoz, ), on the other.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on early FL learning in limited‐exposure classrooms, however, has painted a different picture, indicating little advantage for an early start. This has been attributed to the complex status of age as a “macro‐variable” (Montrul, 2008) associated with myriad socio‐affective, contextual, and cognitive factors, but also to the scarce number of instructional hours per FL per week (see, e.g., Al–Thubaiti, 2010, for Saudi Arabia; Buchholz, 2007, for Austria; Genelot, 1997, for France; Graham et al., 2017, for Great Britain; Jaekel et al., 2017, for Germany; Larson–Hall, 2008, for Japan; Muñoz, 2006, for Catalonia [Spain]; Pfenninger & Singleton, 2017, 2019, for Switzerland; de Wolf, Smit, & Lowie, 2017, for the Netherlands). On this, many proponents of the Critical Period Hypothesis (CPH; e.g., Montrul, 2008) as well as CPH sceptics (like Moyer, 2013, 2014) agree.…”
Section: The Age Issue In Foreign Language Instructionmentioning
confidence: 99%
“…It is significant for learning a foreign language that the language landscape is present in the child's everyday life as often as possible. According to Graham (2017) fifteen minutes a day is more efficient for learning a new language than one learning session a week.…”
Section: Stage Ii: Internalizing the Language Materials And Producing mentioning
confidence: 99%